Optimizing Hole Cleaning in Eccentric Geometries: A Review of Mechanisms and Influencing Factors - Mohamed Y. Saad; Adel M. Salem; Omar Mahmoud (Engineering Research: Perspectives on Recent Advances Vol. 6, 2025)
To keep up with the growing demand for energy, directional well drilling techniques are widely employed. Horizontal and deviated wells provide larger drainage areas through reservoirs compared to vertical wells. These drilling methods are widely used to meet the increasing demand for energy and provide additional fuel resources. However, inadequate hole cleaning (HC) has become a significant challenge, leading to potential technical issues such as reduced rate of penetration, excessive torque and drag, or even stuck pipe. Poor hole cleaning is attributed to the accumulation of cuttings that may lead to a reduction in the rate of penetration (ROP) in both horizontal and inclined wells, as well as an increase in friction and torque on the eccentric drill string. Additionally, the deviated annulus can often be eccentric due to the weight of the drill string and intense drilling oscillations during directional drilling, making the HC process more complex. Various HC models and downhole technologies are utilized to improve the transport of cuttings from deviated and horizontal wellbores to the surface. This paper explores the latest equipment and downhole assemblies used in these wells, as well as the mechanisms behind cuttings transport in different wellbore trajectories. It also provides an extensive review of key influencing factors, including rheological and geometrical properties, drilling operational parameters, cuttings characteristics, and sweeps. The modeling and geometrical analysis of eccentric annuli are evaluated and presented graphically. Moreover, the potential of experimental, intelligent, and computational fluid dynamics (CFD) applications in real-time operations is discussed, along with their recent advancements. Finally, the paper concludes with recommendations to address HC challenges, guide the selection of assemblies and drilling fluids, and optimize drilling operations for more effective hole cleaning in directional and eccentric wells. The study recommends that future studies focus on improving the accuracy of cuttings removal and drilling fluid performance through advanced simulation models, and investigating the impact of eccentricity and flow regimes on HC in deviated and horizontal wells.